Isolation and identification of bioactive compounds from chloroform fraction of methanolic extract of Carissa opaca roots. Issue 17 (1st September 2016) - Ahmed, Dildar; Fatima, Khaizran; Saeed, Ramsha; Masih, Rashid
Abstract: Carissa opaca is a shrub known for its variety of medicinal applications. This study reports isolation and identification of four chemical compounds from its roots for the first time. The methanolic extract of the roots was fractionated into various solvents with increasing polarity. Chloroform fraction was subjected to column and thin layer chromatography to ultimately yield 2 H -cyclopropanaphthalene-2-one, 7-hydroxy-6-methoxy-2 H -1-benzopyran-2-one, 3-(4-methoxyphenyl)-2, 6-dimethylbenzofuran and 5(1 H )-azulenone, 2, 4, 6, 7, 8, 8a-hexahydro-3, 8-dimethyl-4-(1-methylethylidene)-, (8S-cis). They were identified by GC–MS analysis. The compounds exhibited considerable antimicrobial activities against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Candida albicans and Aspergillus niger with zones of inhibition ranging from 10 to 13 mm as compared to the standard drug amoxicillin with zones of inhibition 13–17 mm under the similar conditions. In conclusion, the roots of C. opaca can provide new leads for future antimicrobial drugs. Abstract :